Estudio de prefactibilidad para la instalación de una planta de gelatina a base de agar-agar - Escalante Silva Santisteban, Gonzalo (2019)
The objective of the present prefeasibility study is to find technical and economic viability in the installation of a plant to produce agar-based gelatin powder. The reasons for which this was sought to investigate were two: first, the gelatin market was limited in terms of raw materials on which this product was based, since all gelatin products sold are made from collagen and this, as will be seen in the present study, does not have significant nutritional qualities as agar agar has. Secondly, the types of algae used to extract the agar agar are abundant in the Peruvian coast, which facilitates the continuous supply and allows to cover the new demands that will be created. Finally, it is expected to create a viable substitute for collagen gelatin and at the same time develop the Peruvian raw material processing industry for the production of healthy food. The latter, focusing on the fact that Peru is a country of a vast volume of natural resources and is usually the most important provider of most of them worldwide; however, it has a deficit in technological development that slows down its growth rate.